2022
DOI: 10.1097/acm.0000000000004510
|View full text |Cite
|
Sign up to set email alerts
|

The Performance and Trajectory of Medical Students With Disabilities: Results From a Multisite, Multicohort Study

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…(It is counterintuitive that a group more likely to fail are just as likely to complete the course successfully, but this juxtaposition does not take into account the length of time taken to complete the course.) Another recent study has documented poorer performance in students with cognitive/learning disability compared with matched controls, as well as a measurable impact of accommodation on academic performance 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(It is counterintuitive that a group more likely to fail are just as likely to complete the course successfully, but this juxtaposition does not take into account the length of time taken to complete the course.) Another recent study has documented poorer performance in students with cognitive/learning disability compared with matched controls, as well as a measurable impact of accommodation on academic performance 29…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study has documented poorer performance in students with cognitive/learning disability compared with matched controls, as well as a measurable impact of accommodation on academic performance. 29 …”
Section: Discussionmentioning
confidence: 99%
“…19 The 'State' of disability inclusion can be measured by systemic barriers to access, which lead to disparate outcomes for trainees with disabilities compared to their non-disabled peers. 20 These barriers are present in several domains, including: admissions, 3,21,22 instruction, 18 process, 16 access to accommodation in medical training and licensure exams, 23,24 lack of knowledge regarding reasonable and appropriate accommodation/ adjustments 3,16 and discriminatory practices for physician licensure. 24,25 In the context of an ableist and historically hostile environment.…”
Section: Deming's Point 3: Cease Dependence On Inspection To Achieve ...mentioning
confidence: 99%
“…A study2 of the Membership of the Royal College of Surgeons Part A and B examinations from the United Kingdom showed that candidates with disabilities had similar pass rates to their none-disabled colleagues in clinical examinations (part B) but had significantly lower pass rates on formal, written examinations (part A). This is particularly concerning, given findings from Meeks et al 3 that suggest poor academic performance of medical students with disabilities is associated with a lack of academic accommodations. Given these findings, it is reasonable to question whether the current structures related to academic accommodations are adequate and whether current examinations truly reflect clinical acumen among this population.…”
mentioning
confidence: 98%